Answer:
![y(x)\ =\ √(x)[C_1cos(√(3))/(2)logx+C_2sin(√(3))/(2)logx]](https://img.qammunity.org/2020/formulas/mathematics/college/kzz7mv4ujpc5r5urztekq3pps3rfffakpr.png)
Explanation:
Given differential equation is
(1)
Let's assume that
![x=e^t](https://img.qammunity.org/2020/formulas/mathematics/college/448s1vv6hr0m2dfptzf6dezc24lw2skvbs.png)
![=>\ t\ =\ logx](https://img.qammunity.org/2020/formulas/mathematics/college/afjwpu5tqhedro2szr1i7sq7iv4l4s7f0l.png)
then,
![(dx)/(dt)=e^t](https://img.qammunity.org/2020/formulas/mathematics/college/82q2q3m9spmw0ol6fa7hv58btjmxli0umt.png)
![and\ (d^2x)/(dt^2)=e^t](https://img.qammunity.org/2020/formulas/mathematics/college/3ctlfqvk2bjwplqvare83e91wmmvhfuar2.png)
We can write,
![(dy)/(dx)=(dy)/(dt).(dt)/(dx)](https://img.qammunity.org/2020/formulas/mathematics/college/o0a1sl7wscssaf690c0eelg2j781x8kjcf.png)
![=e^(-t)(dy)/(dt)](https://img.qammunity.org/2020/formulas/mathematics/college/w2zpib6zdsdv8o1ujes25tt5qkz55eg1kk.png)
Similarly,
![(d^2y)/(dt^2)=(d^2y)/(dt^2).(dt^2)/(dx^2)](https://img.qammunity.org/2020/formulas/mathematics/college/g2ruwq430wty1m8gcf6c4fglxeydge6dm4.png)
![=e^(-2t).(d^2y)/(dt^2)](https://img.qammunity.org/2020/formulas/mathematics/college/3eljmj7y33847fg43n0twvr3a9gh3zbkxl.png)
Putting these values in equation (1), we will get
![e^(2t).e^(-2t).(d^y)/(dt^2)-e^t.e^(-t)(dy)/(dt)+y=0](https://img.qammunity.org/2020/formulas/mathematics/college/vfsga0y9c7y5znnbd1mlc1a29pdyvf1mse.png)
![=>(d^2y)/(dt^2)-(dy)/(dt)+y=0](https://img.qammunity.org/2020/formulas/mathematics/college/dfqr8qubl97w7npr9ckuwvc1nm3xgacedi.png)
So, the characteristics equation can be given as
![D^2-D+1=0](https://img.qammunity.org/2020/formulas/mathematics/college/j0i1rfqbu24lrui66xw2zu3a6kp6yjr6s0.png)
![=>D\ =\ (1+√(1-4))/(2)\ or\ (1-1√(1-4))/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/9nz2ku6f9o828dxevw39f3r6ha5sn6f1qe.png)
![=>D=\ (1)/(2)+i(√(3))/(2)\ or\ (1)/(2)-i(√(3))/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/z4x8rqt5w69qk8029l233ovik07qdk2633.png)
Hence, the general solution of the equation can be give by
![y(t)\ =\ e^{(t)/(2)}[C_1cos(√(3))/(2)t+C_2sin(√(3))/(2)t]](https://img.qammunity.org/2020/formulas/mathematics/college/5lsuaqz1igq1c5t1s8mha991nikr4u3298.png)
Now, by putting the value of t in above solution, we will have
![y(x)\ =\ e^{(1)/(2)logx}[C_1cos(√(3))/(2)logx+C_2sin(√(3))/(2)logx]](https://img.qammunity.org/2020/formulas/mathematics/college/s1h3pf532091ty9ah5hgb4bgt6nonio1tm.png)
![y(x)=\ √(x)[C_1cos(√(3))/(2)logx+C_2sin(√(3))/(2)logx]](https://img.qammunity.org/2020/formulas/mathematics/college/k7la5h37soyhd37ghx4omyw4by6ilyagzu.png)
Hence, the solution of above given differential equation can be given by
![y(x)=\ √(x)[C_1cos(√(3))/(2)logx+C_2sin(√(3))/(2)logx]](https://img.qammunity.org/2020/formulas/mathematics/college/k7la5h37soyhd37ghx4omyw4by6ilyagzu.png)